Application of real‑time cell analysis biosensor technology for drug cytotoxicity studies in primary lung cancer cells - Mohd Mansor, Ahmad Fairuzabadi; Sedek, Salmah; Nordin, Anis Nurashikin; Mohammad, Mardhiah; Hashim, Yumi Zuhanis Has‑Yun; Wan Nordin, Amir Farid; Goh, Kian Liang; Abdul Azih, Muhammad Naimmuddin; Abdul Razak, Megat Razeem; Ibrahim, Aishah; How, Soon Hin (Springer, 2022)
Biosensing technologies can be used for toxicity studies on cell cultures. The xCELLigence Real-Time Cell Analysis (RTCA) system is a portable label-free detection method with the capability to analyze cellular proliferation, migration, invasion, growth, morphology states, and cytotoxicity of adherent cells in a non-invasive environment. In pharmacological context, most xCELLigence studies were done using cancer cell lines. Hypothetically, implementing the system with primary cell culture can anticipate actions in vivo better than those seen on cell lines. This could potentially provide useful information on how the drug responds to targeted cancer. In this work, we explore the usage of biosensing technology to establish a concept for high-throughput testing of chemotherapeutics agents on primary patient-derived cancer cells. Four self-established primary lung cancer cells (samples A36, A38, A39, and A40) were derived from biopsies of patients, cultured, and tested with cisplatin. The xCELLigence was used to monitor the response of primary lung cancer cells toward diferent concentrations of cisplatin ranging from 1 to 120 μM. Cisplatin was found to be efective at approximately 20 μM after 48 h of exposure with A38 and A39 showing drug resistance behavior at below 20 μM concentration. The IC50 values were between 22.88 to 76.22 μM. This indicates that the RTCA biosensor technology has good potential in predicting the cell’s response to chemotherapy especially when primary cancer cells are used. This approach can be the fundamental reference in the future to support personalized chemotherapy treatment by providing additional information on metastatic behavior, cytotoxic and drug-resistance efects of the cancer cells.